2022
DOI: 10.1111/ele.13984
|View full text |Cite
|
Sign up to set email alerts
|

Failures to disagree are essential for environmental science to effectively influence policy development

Abstract: While environmental science, and ecology in particular, is working to provide better understanding to base sustainable decisions on, the way scientific understanding is developed can at times be detrimental to this cause. Locked-in debates are often unnecessarily polarised and can compromise any common goals of the opposing camps. The present paper is inspired by a resolved debate from an unrelated field of psychology where Nobel laureate David Kahneman and Garry Klein turned what seemed to be a locked-in de-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 157 publications
(187 reference statements)
0
11
0
Order By: Relevance
“…There are, however, a growing number of observations showing marked inter-annual variability in the relative dominance of phytoplankton over submerged plant abundance [21][22][23][24][25][26][27] . As is often the case when theory confronts data 28 the theory has undergone some revisions, including multiple stable states 29 cyclical shifts between states 30 and the presence of the ghosts of long-term transients 24 . In addition, other studies have identified the regular coexistence of clear water and turbid conditions within a single growing season 31,32 .…”
mentioning
confidence: 99%
“…There are, however, a growing number of observations showing marked inter-annual variability in the relative dominance of phytoplankton over submerged plant abundance [21][22][23][24][25][26][27] . As is often the case when theory confronts data 28 the theory has undergone some revisions, including multiple stable states 29 cyclical shifts between states 30 and the presence of the ghosts of long-term transients 24 . In addition, other studies have identified the regular coexistence of clear water and turbid conditions within a single growing season 31,32 .…”
mentioning
confidence: 99%
“…This affects the study of mycorrhizal symbioses as there are significant differences in the focus of AM versus EcM studies, hampering the generation of a unified language to describe them [11,47]. Applying trait-based methods to highly context-dependent mycorrhizal symbioses without a standardized vocabulary is challenging and can result in 'locked-in debates' among researchers that hinder scientific advances [51].…”
Section: Controversy and Disagreement In What Constitutes A Mycorrhiz...mentioning
confidence: 99%
“…As for multiple other very important questions in biology, explanations for hypometric metabolic scaling are unresolved, and we hope that this paper will aid interested scientists in the development of an agreed-upon theory. Doing so requires that participants in the field directly address each other's arguments, recognize the context-dependence of biological processes, and consider multiple hypotheses ( Norberg et al 2022 ). We do not attempt to review all the evidence for and against the various hypotheses, and refer readers to excellent, more comprehensive reviews on this subject ( Glazier 2014 ; White and Kearney 2014 ; 2018 ; Harrison 2018 ; Kozłowski et al 2020 ).…”
Section: General Introduction To Hypometric Metabolic Scalingmentioning
confidence: 99%